2023
DOI: 10.1121/10.0016752
|View full text |Cite
|
Sign up to set email alerts
|

Inter-seasonal comparison of acoustic propagation in a Thalassia testudinum seagrass meadow in a shallow sub-tropical lagoon

Abstract: Acoustic propagation measurements were collected in a seagrass meadow in a shallow lagoon for periods of over 65 h in winter and 93 h in summer. A bottom-deployed sound source transmitted chirps (0.1–100 kHz) every 10 min that were received on a four-receiver horizontal hydrophone array. Oceanographic probes measured various environmental parameters. Daytime broadband acoustic attenuation was 2.4 dB greater in summer than winter, and the median received acoustic energy levels were 8.4 dB lower in summer compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The sounds that contributed to this mean SPL difference seemed largely biological in origin, likely predominantly snapping shrimp snaps (Breder, 1968;Mathews, 2006). Measured transmission loss, however, was similar between the two sites (Figure 6) and, if anything, attenuation would likely be higher at the living shoreline site because of the presence of salt marsh grasses (Arenovski & Howes, 1992;Biggs & Erisman, 2021;Felisberto et al, 2015;Hopson, 2019;Lee et al, 2023;Miksis-Olds & Miller, 2006). The detected increase in mean SPL was, therefore, more likely the result of increased sound-producer abundance and/or sound-production rates (Lillis & Mooney, 2022;Wall et al, 2021).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The sounds that contributed to this mean SPL difference seemed largely biological in origin, likely predominantly snapping shrimp snaps (Breder, 1968;Mathews, 2006). Measured transmission loss, however, was similar between the two sites (Figure 6) and, if anything, attenuation would likely be higher at the living shoreline site because of the presence of salt marsh grasses (Arenovski & Howes, 1992;Biggs & Erisman, 2021;Felisberto et al, 2015;Hopson, 2019;Lee et al, 2023;Miksis-Olds & Miller, 2006). The detected increase in mean SPL was, therefore, more likely the result of increased sound-producer abundance and/or sound-production rates (Lillis & Mooney, 2022;Wall et al, 2021).…”
Section: Discussionmentioning
confidence: 96%
“…Within the salt marsh planting, however, transmission loss would likely be high (Supporting Information Figure S5). Aquatic plant species, such as S. alterniflora that was planted at the living shoreline site, can develop complex gas transport and lacunal allocation systems as well as produce bubbles through photosynthesis, with potentially substantial impacts on sound travel (Arenovski & Howes, 1992; Felisberto et al, 2015; Hopson, 2019; Lee et al, 2023; Maricle & Lee, 2002; Miksis‐Olds & Miller, 2006). In fact, a similar study in freshwater wetland habitats found significant impacts of both distance and vegetation presence on attenuation (Hopson, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seagrasses have aerenchyma tissues with continuous air-filled lacunae in leaves, rhizomes, and roots (Armstrong, 1979; Larkum et al, 1989; Borum et al, 2006; Mckenzie, 2008). The lacunae allow movement of photosynthetic oxygen produced below the leaf epidermis to flow to petioles, stem, rhizomes, and roots (Roberts et al, 1984; Lee et al, 2023) by phase diffusion (Sorrell and Dromgoole, 1987). The lacunae in leaf and rhizome are connected and have diaphragms at the nodes and transitional regions (Larkum et al,1982).…”
Section: Intoductionmentioning
confidence: 99%